A comprehensive review on selective catalytic reduction catalysts for NOx emission abatement from municipal solid waste incinerators. Issue 4 (8th February 2016) - Yan, Qinghua; Yang, Ruoyan; Zhang, Yili; Umar, Ahmad; Huang, Zhanggen; Wang, Qiang
Abstract : Incineration is considered to be an effective disposal method for municipal solid wastes (MSW), which is attracting increasing attention due to its great performance in waste reduction. However, one big problem for incineration process is the release of a number of harmful pollutants. Nitrogen oxide (NOx ) is one of the major pollutants in the exhaust of various combustion processes because it is harmful to both environment and human health. For reducing NOx emission from MSW incinerators flue gases, selective catalytic reduction (SCR) technology has been widely investigated because of its high efficiency, good selectivity, and low cost. Since the gas composition from MSW incinerators is more complex than that from coal‐fired power plants, lots of attention has been paid to making more robust SCR catalysts. The aim of this article is to provide a critical and timely review on the recent progresses of SCR catalysts used for MSW incinerator flue gases. We also discussed the influence of HCl, SO2, alkali metal, phosphorus, arsenic, lead, and so forth on the conversion of NOx to N2 . Moreover, the mechanism and kinetics involved in the SCR of NOx for MSW incinerator flue gases were also discussed. We hope this contribution could shed light on the development of novel catalysts and/or technologies from MSW incinerators flue gases. © 2016 American Institute of Chemical Engineers Environ Prog, 35: 1061–1069, 2016